2019
DOI: 10.1002/ase.1866
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy, the Achille’s Heel of Medical Students. A Systematic Analysis of Educational Strategies for the Teaching of Neuroanatomy

Abstract: Neuroanatomy has been deemed crucial for clinical neurosciences. It has been one of the most challenging parts of the anatomical curriculum and is one of the causes of "neurophobia", whose main implication is a negative influence on the choice of neurology in the near future. In the last decades, several educational strategies have been identified to improve the skills of students and to promote a deep learning. The aim of this study was to systematically review the literature to identify the most effective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 96 publications
(159 reference statements)
0
37
0
Order By: Relevance
“…Nowadays, technological advances have generated many subsidies for teaching. In this sense, there is growing consensus that combinations between technological and pedagogical resources can provide benefits to the performance and, consequently, the learning of the students in the teaching of Human Anatomy (Lochner et al, 2016;Trelease, 2016;Oliveira et al, 2019;Sotgiu et al). This condition is reported by students, who demonstrate that they benefit more from the traditional method when it is accompanied by complementary pedagogical resources, e.g., synthetic models, virtual reality (3D visualization), and multimodal approaches (Papa & Vaccarezza, 2013;Estai & Bunt;Ruzycki et al).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, technological advances have generated many subsidies for teaching. In this sense, there is growing consensus that combinations between technological and pedagogical resources can provide benefits to the performance and, consequently, the learning of the students in the teaching of Human Anatomy (Lochner et al, 2016;Trelease, 2016;Oliveira et al, 2019;Sotgiu et al). This condition is reported by students, who demonstrate that they benefit more from the traditional method when it is accompanied by complementary pedagogical resources, e.g., synthetic models, virtual reality (3D visualization), and multimodal approaches (Papa & Vaccarezza, 2013;Estai & Bunt;Ruzycki et al).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a classical science, it continues to present great relevance in the training of university students in health areas, as professionals will use this knowledge in their practical activities (Ruzycki et al, 2019). In this context, research has been carried out with the aim of verifying the best teaching-learning strategy in Human Anatomy (Estai & Bunt, 2016;Clunie et al, 2018;Sotgiu et al, 2019;Zilverschoon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, we hypothesize that this difference may be due to almost half of the neuroanatomy courses being taught within the gross anatomy courses, similar to Canada (Rockarts et al, 2020). Modernization of this course is needed in Mexico to foster higher learning (Johnson et al, 2012; Palomera et al, 2014; de Faria et al, 2016), including the implementation of other pedagogical tools such as 3D digital modeling and virtual reality (Arantes et al, 2018; Sotgiu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, VR and AR tools have been used to teach basic and advanced neuroanatomy to enhance, or replace, traditional cadaveric dissection. A recent review of studies using different methods to teach neuroanatomy showed that nearly half of these already takes advantage of 3D teaching tools or AR 3 . A cross-over design study was performed to assess the potential benefits of cadaveric versus 3D computer-based learning of neuroanatomy.…”
Section: From Cadaveric Dissections To Computersmentioning
confidence: 99%